Influence of Plastic Endodontic Instruments on the Activation Protocol of Irrigantic Solutions in Chemomechanical Preparation: Literature Review - , Yana Cavalcante de Araújo; , Luildyson Araújo de Almeida; , Bruno Carvalho de Vasconcelos; , Fábio de Almeida Gomes; , Luiz Carlos Trevia Morais Correia Viana; , Alinne Patierry Oliveira Pacífico Feitosa; , Thiago Colares Castelo Branco; , Bernardo Almeida Aguiar (Archives of Current Research International, 2025)
Introduction: The mechanical action in endodontic treatment is performed by endodontic files, and the chemical action by auxiliary solutions. However, both individually are insufficient in cleaning and removing the smear layer. Thus, there was a need to develop techniques for activate the solutions using ultrasound tips or plastic instruments that would assist in this process, for better disinfection of the canals. Aims: Evaluate the effectiveness of plastic endodontic instruments (EDDY, Easy Clean and EndoActivator) in cleaning the root canals and their efficiency in endodontic treatment. Methodology: A search for articles was conducted in the PubMed, Bireme and SciELO databases. The descriptors “Endodontic Irrigation”, “Sonic Irrigation” and “Activation Systems” were used in a cross-search. Articles in both Portuguese and English, from January 2015 to April 2020, were included. Literature review articles that were not relevant to the study were excluded. Of the total of 17 articles found, 5 were duplicates across the platforms, 5 met the exclusion criteria, and 7 were selected for the integrative review. Results: The instruments showed greater efficiency in removing smear layer, biofilm and bacteria present inside the root canal, through activation of auxiliary chemical solutions, such as sodium hypochlorite and EDTA. Discussion: The studies analyzed demonstrate the effectiveness of sonic activation systems in cleaning the root canal. However, despite the advances, there are still limitations in eliminating deep bacteria, indicating the need for complementary methods to optimize clinical results. Conclusion: It can be concluded that the plastic instruments EDDY, Easy Clean and EndoActivator proved to be a good option in the cleaning protocol of root canal systems.